Bioengineered bacterial vesicles as biological nano-heaters for optoacoustic imaging - Vipul Gujrati (Nature Portfolio, 2019)
Bacterial outer membrane vesicles (OMVs) are increasingly used as carriers for drug delivery. Here the authors encapsulate biopolymer melanin into OMVs, extending their use to optoacoustic imaging both in vitro and in vivo, and demonstrate the potential of this tool for photothermal therapy applications.